Hybrid Battery Swapping Station for EV Using Robotic Arms - Ashwin R Saji; Nithin Prasanth; Prarthana U. Kumar; Veena S; Rakhi Das (International Journal of Advanced Robotics and Automation Technology, 2024)
The Robotic Arm-Based Battery Swapping System indeed marks a significant stride in merging technology and sustainability. Its integration of robotics, computer vision, and renewable energy positions it as a ground breaking solution, reshaping the landscape of electric vehicle charging. This automated approach not only tackles inefficiencies in current methods but also serves as a blueprint for future advancements in the domain. The inefficiencies inherent in conventional electric vehicle battery replacement methods, characterized by time-consuming processes and manual interventions, are precisely what the Robotic Arm-Based Battery Swapping System aims to address. Through the integration of precise robotics, computer vision, and sustainable energy sources, the project seeks to provide a streamlined, precise, and eco-friendly solution in response to the growing demand for improved efficiency and environmental alignment in the electric mobility landscape. Focuses on the precision and automation of battery swapping processes in electric vehicles. The project features a robotic arm with 3D-printed components and servo motors for accurate movements. The system includes a computer vision system using OpenCV for battery recognition and positioning. Safety measures are implemented through the use of a smoke sensor and temperature monitoring with voice feedback. The project also incorporates a solar charging system, consisting of a solar panel and charge controller, to reduce reliance on conventional power grids and promote sustainability. The system's performance can be monitored through a 16x2 LCD display, which provides real-time information on charging status and system parameters. The event of potential hazards, the smoke sensor promptly triggers responsive actions, ensuring the swift and effective mitigation of risks.
Keywords: Computer vision; LCD; OpenCV; RFID; Streamline; Swapping; Triggers